Can data cross frontiers? Challenges and drivers for cross-border data sharing for disaster risk reduction - Adrot, Anouck; Isaac, Henri; Ritouret, Salome (Frontiers in Communication, 2025)
Data sharing is a key driver of disaster risk reduction (DRR) and supports the resilience of cross-border regions. However, data sharing across borders remains challenging, and only a limited number of regions have significantly progressed in this area. A better understanding of the challenges of data sharing in cross-border DRR ecosystems is therefore needed but remains overlooked in the literature. This research, which is based on a qualitative and collaborative design, focuses on the Italy–France border, which has been pursuing efforts to create a cross-border data ecosystem for DRR in recent years. This study consists of a comprehensive analysis, which is primarily based on qualitative interviews, observations, and archive analyses. It outlines how the cross-border setting exacerbates the challenges of data sharing for DRR. Cross-border DRR actors struggle to build trust around the data and adopt a unified data strategy across borders. However, in the face of these challenges, DRR actors are gradually transforming their DRR practices by incorporating cooperative, trustful, and inclusive relationships. Our findings contribute to a more situated understanding of data sharing at borders and call for greater consideration of border settings and the agency from practitioners involved in data sharing for international DRR.